2011
DOI: 10.1615/plasmamed.2012006389
|View full text |Cite
|
Sign up to set email alerts
|

A Nitric Oxide Producing Pin-to-Hole Spark Discharge Plasma Enhances Endothelial Cell Proliferation and Migration

Abstract: Nitric oxide (NO) plays a key role in vascular functions and wound healing. A pin-to-hole spark discharge (PHD), which primarily produces NO, recently emerged as an effective tool for medical applications. We therefore investigated whether PHD plasma-produced NO could promote angiogenesis. PHD plasma equipped with a curved tube extension was used to treat a saline solution and porcine aortic endothelial cells in vitro. Both NO and nitrite increased linearly in plasma-treated phosphate buffered saline, and NO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…chronic wounds and cancers. It has been shown through in vitro cell studies and in vivo animal experiments that cold atmospheric plasma, herein referred to as plasma, might accelerate wound healing by stimulation of cell growth and migration [1][2][3][4][5][6][7][8][9][10][11], and also decontaminate infected wounds through targeted destruction of bacterial cells [12][13][14][15][16][17][18][19][20][21][22]. Similar results have been obtained in clinical studies where the efficacy of plasma in wound decontamination and healing has been demonstrated [23][24][25][26].…”
Section: Introductionsupporting
confidence: 56%
“…chronic wounds and cancers. It has been shown through in vitro cell studies and in vivo animal experiments that cold atmospheric plasma, herein referred to as plasma, might accelerate wound healing by stimulation of cell growth and migration [1][2][3][4][5][6][7][8][9][10][11], and also decontaminate infected wounds through targeted destruction of bacterial cells [12][13][14][15][16][17][18][19][20][21][22]. Similar results have been obtained in clinical studies where the efficacy of plasma in wound decontamination and healing has been demonstrated [23][24][25][26].…”
Section: Introductionsupporting
confidence: 56%
“…The field of plasma medicine possesses a high innovation potential and the treatment of chronic wounds with plasma is particularly promising as numerous studies have suggested in vitro and in vivo . In addition to the plasma's antiseptic activity, some cells are eliminated by plasma‐induced apoptosis, and the proliferation and migration of fibroblasts and keratinocytes as well as angiogenesis is promoted . Mild inflammatory stimuli in, for example, immune cells and skin cells, may help the chronic wound to transit from stagnation into the phase of acute inflammation, to subsequently mediate wound healing.…”
Section: Plasma Medicinementioning
confidence: 99%
“…Cold physical plasma, from hereon named plasma, is a partially ionized gas at body temperature [26]. This multi-component system is releasing a variety of ROS/RNS, such as, nitric oxide, superoxide, and singlet oxygen [27][28][29]. At present, three medical plasmas have received accreditation as medical devices [30].…”
Section: Introductionmentioning
confidence: 99%